Clinical significance of detecting serum melatonin and SBDPs in brain injury in preterm infants - Caixia Yan; Binghong Zhang (Pediatrics and Neonatology)
Background: To investigate the clinical values of serum melatonin and αII spectrin cleavage products (SBDPs) in assessing the severity of brain injury in preterm infants. Methods: Sixty-four premature infants in total were selected and classified into the brain injury group (BI, n = 30) and the non-brain injury group (CON, n = 34) according to cranial imaging examination. The serum melatonin and SBDPs were detected by ELISA. All the preterm infants were received NBNA testing at 40 weeks of corrected gestational age. Results: The levels of melatonin and SBDPs in the BI group were significantly higher than the CON group (p < 0.05) and the levels in the infants with severe brain injury were significantly higher than those with mild brain injury (p < 0.05), as well as exhibiting a negative correlation with the NBNA score at 40 weeks of corrected gestational age (p < 0.05). Conclusions: Detecting melatonin and SBDPs has clinical value in diagnosing and assessing the severity of brain injury in preterm infants. Key Words: brain injury, melatonin, preterm infants, αII spectrin cleavage products